Long Non-Coding RNAs: The Regulatory Mechanisms, Research Strategies, and Future Directions in Cancers - Gao, Na; Li, Yueheng; Li, Jing; Gao, Zhengfan; Yang, Zhenzhen; Li, Yong; Liu, Hongtao; Fan, Tianli (Frontiers in Oncology, 2020)
Abstract: The development and application of whole genome sequencing technology has greatly broadened our horizons on the capabilities of long non-coding RNAs (lncRNAs). LncRNAs are more than 200 nucleotides in length and lack protein-coding potential. Increasing evidence indicates that lncRNAs exert an irreplaceable role in tumor initiation, progression, as well as metastasis, and are novel molecular biomarkers for diagnosis and prognosis of cancer patients. Furthermore, lncRNAs and the pathways they influence might represent promising therapeutic targets for a number of tumors. Here, we discuss the recent advances in understarding of the specific regulatory mechanisms of lncRNAs. We focused on the signal, decoy, guide, and scaffold functions of lncRNAs at the epigenetic, transcription, and post-transcription levels in cancer cells. Additionally, we summarize the research strategies used to investigate the roles of lncRNAs in tumors, including lncRNAs screening, lncRNAs characteristic analyses, functional studies, and molecular mechanisms of lncRNAs. This review will provide a short but comprehensive description of the lncRNA functions in tumor development and progression, thus accelerating the clinical implementation of lncRNAs as tumor biomarkers and therapeutic targets.